Dynamic necking of a near α titanium alloy at high strain rates: experiments and modelling - Zhang, L-H; Pellegrino, A; Petrinic, N (Elsevier, 2020)
The tensile behaviour of near α Ti3Al2.5 V alloy, conceived for applications in aerospace and automotive engineering, is characterized from quasi-static to high strain rates. The material is found to present noticeable strain rate sensitivity. The dynamic true strain rate in the necking cross-section reaches values up to ten times higher than the nominal strain rate. It is also observed that beyond necking the dynamic true stress-strain curves present limited rate dependence. The experimental results at different strain rates are used to determine a suitable constitutive model for finite element simulations of the dynamic tensile tests. The model predicts the experimentally macroscopic force-time response, true stress-strain response and effective strain rate evolution with good agreement.